2018
DOI: 10.1186/s12859-018-2076-7
|View full text |Cite
|
Sign up to set email alerts
|

NoLogo: a new statistical model highlights the diversity and suggests new classes of Crm1-dependent nuclear export signals

Abstract: BackgroundCrm1-dependent Nuclear Export Signals (NESs) are clusters of alternating hydrophobic and non-hydrophobic amino acid residues between 10 to 15 amino acids in length. NESs were largely thought to follow simple consensus patterns, based on which they were categorized into 6–10 classes. However, newly discovered NESs often deviate from the established consensus patterns. Thus, identifying NESs within protein sequences remains a bioinformatics challenge.ResultsWe describe a probabilistic representation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Hence, experimental identification and validation is mandatory. However, since mutational analysis of HSV1 NESs predicted by the NES pattern and by NetNES confirmed their functionality in all cases, the major strength of a range of developed NES prediction algorithms may currently lie in the detection of the relevant export signals in proteins known to be exported.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Hence, experimental identification and validation is mandatory. However, since mutational analysis of HSV1 NESs predicted by the NES pattern and by NetNES confirmed their functionality in all cases, the major strength of a range of developed NES prediction algorithms may currently lie in the detection of the relevant export signals in proteins known to be exported.…”
Section: Discussionmentioning
confidence: 93%
“…Initially, NES prediction was limited to two bioinformatic tools, the NES pattern and the NetNES (http://www.cbs.dtu.dk/services/NetNES ). More recently, other bioinformatic tools were developed including the LocNES algorithm (http://prodata.swmed.edu/LocNES/LocNES.php ). Comprehensive analysis of all HSV1 tegument proteins using the LocNES revealed that, with few exceptions (pUL41, pUS2, pUS11), most HSV1 tegument proteins were predicted to contain a leucine‐rich NES with a score >0.200 (Table ; Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like nuclear import, shuttling proteins from the nucleus back to the cytoplasm is established by a nuclear export signal (NES) that is recognized by exportins such as CRM1. A wellcharacterized NES is the export motifϕχ (2)(3) ϕχ (2)(3) ϕχϕ (where ϕ represents one of the hydrophobic residues L, V, I, F or M and χ is any residue) [92,93], but this consensus pattern has been progressively expanded and computational methods have been addressed to further model the sequence diversity of NESs [93][94][95][96][97][98][99][100].…”
Section: Dynamic Localization Of Fcov 3bmentioning
confidence: 99%